PERAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN DALAM MENANGGAPI TANGGUNG JAWAB PELAKU USAHA TERHADAP KELUHAN KONSUMEN - Pasha Athallah Rasyad; Reva Fitri Ramadani (Cahaya Ilmu Bangsa, 2024)
Law No. 8 of 1999 on Consumer Protection plays a significant role in ensuring legal certainty for consumers and encouraging business actors to fulfill their responsibilities. This law provides a legal framework for consumers to protect their rights, including the right to accurate information, comfort, safety, and compensation for losses arising from transactions involving goods or services. Article 7 of the Consumer Protection Act regulates various obligations of business actors, such as acting in good faith, providing truthful information, ensuring product quality meets standards, and offering compensation in case of violations. This study examines the effectiveness of the Consumer Protection Act in creating a balance between consumers and business actors. Using a normative juridical method, the study concludes that optimizing socialization efforts and fostering collaboration among consumers, business actors, and the government is essential to ensure consumer protection and fairness in business transactions.